EnrichKit: a multi-omics tool for livestock research - Liu, Lihe; Peñagaricano, Francisco (Frontiers in Genetics, 2025)
The increasing applications of omics technologies in livestock research highlights the need for tools capable of interpreting preliminary signals, such as mapping genomic coordinates to gene features and annotating gene lists for functional characterization. These tools should effectively leverage various biological databases for comprehensive analysis. Additionally, the development of user-friendly interfaces is essential to broaden the accessibility and enable a wider range of users to contribute more effectively to the field of livestock genomics. EnrichKit provides friendly graphical user interface and superior efficiency in data management and computational analysis by integrating various public databases and statistical algorithms. Its functionalities are showcased through applications in DNA methylation analysis, gene co-expression network analysis, and differential gene expression analysis. The comparative analysis with existing tools underscores EnrichKit advantages in terms of species-specific gene-set libraries and user accessibility. EnrichKit significantly advances the interpretation of omics studies in livestock genomics. Its tailored approach for species-specific analysis, combined with a comprehensive computational framework, positions it as a valuable tool for researchers. The potential of EnrichKit to transform livestock genomics research is evident, opening avenues for future enhancements and broader applications in the livestock omics research field.